HUMAN RESOURCE DEVELOPMENT IN ELEMENTARY SCHOOLS THROUGH CONTINUOUS TRAINING AND ACADEMIC SUPERVISION - Uswah; Nikem Kurnia Ningsih; Zakiyah; Nurul Setiani; Siska Sukma Awalia (RADJA PUBLIKA, 2025)
The development of human resources (HR) at the elementary school level plays a crucial role in improving the quality of basic education. This study aims to evaluate the effectiveness of continuous professional development and academic supervision as strategies for enhancing teacher professionalism. Using a descriptive qualitative method with a case study approach conducted in several public and private elementary schools, the findings reveal that training programs based on teachers' real needs significantly improve their pedagogical and professional competencies. Meanwhile, academic supervision that is constructive and consistently implemented contributes positively to improving classroom instructional practices. The integration of both strategies creates a dynamic school ecosystem that fosters a culture of reflection, innovation, and continuous improvement in teaching performance. The study recommends the need for strong institutional support and close collaboration among school principals, supervisors, and teachers to ensure sustainable HR development that impacts student learning outcomes.